P-Selectin Targeted Dexamethasone-Loaded Lipid Nanoemulsions: A Novel Therapy to Reduce Vascular Inflammation - Viorel Simion; Cristina Ana Constantinescu; Daniela Stan; Mariana Deleanu; Monica Madalina Tucureanu; Elena Butoi; Ileana Manduteanu; Maya Simionescu; Manuela Calin (Mediators of Inflammation)
Inflammation is a common process associated with numerous vascular pathologies. We hypothesized that targeting the inflamed endothelium by coupling a peptide with high affinity for P-selectin to the surface of dexamethasone-loaded lipid nanoemulsions will highly increase their specific binding to activated endothelial cells (EC) and reduce the cell activation. We developed and characterized dexamethasone-loaded lipid nanoemulsions directed towards P-selectin (PLN-Dex) and monitored their anti-inflammatory effects in vitro using cultured EC (EA.hy926 cells) and in vivo using a mouse model of acute inflammation [lipopolysaccharides (LPS) intravenously administered in C57BL/6 mice]. We found that PLN-Dex bound specifically to the surface of activated EC are efficiently internalized by EC and reduced the expression of proinflammatory genes, thus preventing the monocyte adhesion and transmigration to/through activated EC. Given intravenously in mice with acute inflammation, PLN-Dex accumulated at a significant high level in the lungs (compared to nontargeted nanoemulsions) and significantly reduced mRNA expression level of key proinflammatory cytokines such as IL-1β, IL-6, and MCP-1. In conclusion, the newly developed nanoformulation, PLN-Dex, is functional in vitro and in vivo, reducing selectively the endothelium activation and the consequent monocyte infiltration and diminishing significantly the lungs’ inflammation, in a mouse model of acute inflammation.